APLIKASI AUGMENTED REALITY PENGENALAN HEWAN BERBASIS ANDROID MENGGUNAKAN LIBRARY VUFORIA - I Made Pasek Pradnyana Wijaya (Program Studi Sistem Informasi, Universitas Banten Jaya, 2022)
This world consists of various kinds of living things, there are humans, animals and plants. There are many types of animals in this world. In contrast to the declining animal species, computer technology continues to evolve over time. Computer technology helps a lot in the learning of school children and early childhood. Learning applications are now very developed and easy to find, for example learning applications for smartphone devices. Augmented reality technology is one that is currently being developed and applied. Augmented reality has a positive impact with its potential to project objects such as text, images, videos, and 3D objects in the real world. Application development using augmented reality technology requires a marker. Markers can be in the form of 2D images, locations, objects around us, or in the form of text. Vuforia SDK is a software that can detect an image or text. In this study, the marker used is no longer in the form of an image, but the marker used is in the form of print-out text. The concept is that users simply type the name of the animal on another device or are allowed to print the name of the animal, then scan it with a device that has this augmented reality application installed. This application was built using the waterfall method. Testing is done by using the blackbox technique. The result of this research is the application of augmented reality animal recognition with this print-out textmarker can run well.